Grêmio estudantil em São Paulo um estudo de caso em duas escolas da rede pública estadual - Canhadas, Diogo [UNIFESP] (2019)
The present work aimed to investigate the perception of principals, teachers and students of two public state schools on the student council’s role and activities. For this, a case study was carried out, which included interviews, documentary analysis and participant observation in order to understand possible tensions, conflicts and divergences involving the student council’s activities. It was verified that the students councils are the main tool of political action of the students interviewed and that there was no integration of the student's councils into pedagogical projects. The state public policies as they were developed and applied in the observed schools have resulted in student’s councils far from a democratic and emancipatory formation, unlike what is propagated in the institutional communications of the Education Department of the State of Sao Paulo.